AL-QUR'AN DAN MATERIAL GENETIK DALAM SEL KELAMIN PRIA PENENTU JENIS KELAMIN BAYI - Muchtaromah, Bayyinatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2007)
In many verses of al-Qur'an, men are called to pay their attention to understand how they were created. Human creation and incredible aspects followed were strongly mentioned in many verses in detail until it's impossible for anyone who lived in the seventh century to recognize it. One of them was the information saying that the determinant of baby gender is the spermatozoa coming from men sperm. Allah said in his verse: